Beveridge Report (copy letter) - Watson, John Forbes, Sir
1943-01-20 1943 1940s 2 pages I am doing now will meet the views of the Council, but I had the feeling that my first effort was rather strong meat to those who had studied the "Beveridge" Report through the newspaper views and not through their own reading of it. What I am anxious to do now is to get the revised Statement out in time for those who come here on the 29th. I will send you a copy, for your own personal information, when I send it out to the members of the Council, and meanwhile I would wish to thank you again for having written me. Believe me, Yours sincerely, [ ] PS. I enclose of copy of the Evidence submitted to the Beveridge Committee. (Sgd) JFW R. Gresham Cooke, Esq., The United Steel Companies, Ltd., 17, Westbourne Road, Sheffield, 10. 200/B/3/2/C216/5/99